Adenovirus load correlates with respiratory disease severity among hospitalized pediatric patients. (August 2020) - Goikhman, Yaniv; Drori, Yaron; Friedman, Nehemya; Sherbany, Hilda; Keller, Nathan; Mendelson, Ella; Pando, Rakefet; Mandelboim, Michal
Highlights: Adenoviral load in respiratory samples positively correlate with disease severity. According the 3-group model Ct values of adenovirus can serve as a predictor of disease severity. Ct values of various respiratory viruses were found frequently higher in hospitalizes patients. Abstract: Objectives: Human adenoviruses (HAdVs) are common pathogens that can cause respiratory, gastrointestinal and other infections. We investigated the correlation between adenovirus viral load in clinical respiratory samples and the respiratory disease severity in pediatric patients. Methods: Medical records of patients hospitalized in the Sheba Medical Center (SMC) with confirmed adenovirus infection were retrospectively analyzed. The possible correlation between disease severity score and Real time PCR 'cycle threshold' (Ct), a proxy of viral load, was assessed in patients aged 9 years and under. In addition, Ct values of hospitalized versus community-care patient samples, positive for various respiratory viruses including adenovirus, were compared. Results: Adenovirus load in respiratory samples, as measured by Ct values, was found to be negatively correlated with respiratory disease severity in hospitalized pediatric patients aged under 9 years. Moreover, hospitalized patients presented with significantly higher Ct levels for various respiratory viruses as compared to community-care patients. Conclusion: In this study we found a correlation between Ct values obtained from adenovirus q-PCR analysis of respiratory clinical samples and disease severity in patients aged 9 years and under. Such finding may serve as a predictor of respiratory disease course in pediatric patients and will be beneficial for the differential diagnosis and treatment of pediatric patients.